Gender differences in viral infection after repeated exercise stress - Brown, A. S.; Davis, J. M.; Murphy, E. A.; Carmichael, M. D.; Ghaffar, A.; Mayer, E. P. (Medicine & Science in Sports & Exercise, 2004)
Fatiguing exercise can increase susceptibility to respiratory infection after intranasal inoculation with herpes simplex virus-1 (HSV-1) in male mice. Although gender differences in susceptibility to certain pathogens do exist, it is unknown whether female mice will respond differently than males in response to strenuous exercise and HSV-1 infection. PURPOSE: To test the effects of gender on susceptibility to HSV-1 respiratory infection after repeated exhaustive exercise. METHODS: Male (N = 86) and female (N = 89) CD-1 mice (approximately 60 d old) were randomly assigned to exercise (Ex) or control (C) groups. Exercise consisted of 3 d of treadmill running at 36 m x min(-1) at 8% grade until volitional fatigue (135 +/- 5min). Fifteen minutes after the last bout of exercise, Ex and C mice were inoculated intranasally with a standard dose (LD30) of HSV-1. Mice were monitored for 21 d for morbidity (time to sickness and symptom severity) and mortality. RESULTS: Run time to fatigue was significantly longer in females than males (P = 0.027). Significant gender differences in susceptibility to infection were found after exercise stress. In males, exercise stress resulted in increased morbidity (66%, P < 0.05) and mortality (30%, P < 0.05) whereas in females, exercise stress only resulted in increased morbidity (66%, P < 0.05). CONCLUSION: Results suggest that although males and females have similar morbidity rates after infection and exercise stress, females recover to a greater extent and are ultimately better protected from death.